Prevalence of and risk factors for postoperative complications after lower third molar extraction: A multicenter prospective observational study in Japan. Issue 32 (12th August 2022) - Yamada, Shin-ichi; Hasegawa, Takumi; Yoshimura, Nobuhiko; Hakoyama, Yusuke; Nitta, Tetsuya; Hirahara, Narihiro; Miyamoto, Hironori; Yoshimura, Hitoshi; Ueda, Nobuhiro; Yamamura, Yoshiko; Okuyama, Hideki; Takizawa, Atsushi; et al.
Abstract : Lower third molar extraction is the most common surgical treatment among routine dental and oral surgical procedures. while the surgical procedures for lower third molar extraction are well established, the difficulty of tooth extraction and the frequency of postoperative complications differ depending on the patient's background. To establish a management protocol for the lower third molars, the prevalence of and risk factors for postoperative complications after lower third molar extraction were investigated in a large number of Japanese patients in a multicenter prospective study. During 6 consecutive months in 2020, 1826 lower third molar extractions were performed at the 20 participating institutions. The medical records of the patients were reviewed, and relevant data were extracted. The prevalence of and risk factors for postoperative complications were analyzed. The prevalence of postoperative complications after lower third molar extraction was 10.0%. Multivariate analysis indicated that age (≤32 vs >32, odds ratio [OR]: 1.428, 95% confidence interval [95% CI]: 1.040–1.962, P < .05), the radiographic anatomical relationship between the tooth roots and mandibular canal (overlapping of the roots and canal vs no close anatomical relationship between the roots and the superior border of the canal, OR: 2.078, 95% CI: 1.333–3.238, P < .01; overlapping of the roots and canal vs roots impinging on the superior border of the canal, OR: 1.599, 95% CI: 1.050–2.435, P < .05), and impaction depth according to the Pell and Gregory classification (position C vs position A, OR: 3.7622, 95% CI: 2.079–6.310, P < .001; position C vs position B, OR: 2.574, 95% CI: 1.574–4.210, P < .001) are significant independent risk factors for postoperative complications after lower third molar extraction. These results suggested that higher age and a deeply impacted tooth might be significant independent risk factors for postoperative complications after lower third molar extraction.